Recurrent diffuse gastric bleeding as a leading symptom of gastrointestinal AL amyloidosis - Franck, Caspar; Venerito, Marino; Weigt, Jochen; Roessner, Albert; Malfertheiner, Peter (Zeitschrift für Gastroenterologie, 2017)
Amyloidosis is a rare disease (incidence about 0.8/100 000) characterized by extracellular tissue deposition of fibrils composed of low molecular weight subunits of a variety of serum proteins. Clinical manifestations are largely determined by the type of precursor protein, the tissue distribution and the amount of amyloid deposition. Gastrointestinal (GI) manifestations of amyloidosis are even more uncommon (3 % of all amyloidosis patients). Symptoms of GI amyloidosis are nonspecific, heterogeneous, and include weight loss, GI bleeding, heartburn, early satiety, diarrhea and abdominal pain. The histopathological examination of biopsy specimens from the GI tract leads to the diagnosis.Herein we report the case of a 63-year-old woman with recurrent diffuse gastric bleeding. Endoscopic biopsies revealed distinct amyloid deposits in the mucosa of the stomach. Further histochemical assessment confirmed systemic light chain (AL) amyloidosis with clinically predominant gastrointestinal manifestation. An induction therapy with bortezomib and dexamethasone was initiated.Our report illustrates the importance of the multidisciplinary approach for diagnosis and management of AL amyloidosis. Current treatment of systemic AL amyloidosis is based on cytostatic targeting of immunoglobulin producing plasma cells. Therapeutic options are limited and highly toxic, making the development of novel treatment approaches an urgent need.
Keywords: AL-Amyloidose; gastrointestinale Amyloidose; gastrointestinale Blutung; monoklonale Gammopathie; Therapie